Pemberdayaan UMKM Ikan Asin melalui Laporan Keuangan Mikro: Studi Kasus Desa Sungai Bangkal - Nurparidah; Redhana Aulia; Isnaniah, Isnaniah; Farah Hafizha (PT. Karya Inovatif Nusantara, 2026)
BEM Impact Community Empowerment Activities in Sungai Bangkal Village, Sungai Tabuk District, Banjar Regency, South Kalimantan were carried out on 9 October–18 December 2025 with a participatory approach from two main partners, namely the Farmers Group and the Posyandu Group, through the integration of clean water ultrafiltration technology, household food security and digital literacy training. Digital literacy training activities were carried out as an effort to empower salted fish processed MSMEs in facing the challenges of low added value, weak financial records and limited market access. This research uses a descriptive qualitative approach through observation, interviews and documentation. The results of the activity show that selling salted fish can increase the income of the residents of Sungai Bangkal Village. Educate an important understanding regarding the calculation of production costs as a whole so that MSMEs can set rational and profitability-oriented selling prices. Meanwhile, the integration of clean and neat packaging, e-commerce and Google Maps has been proven to increase product competitiveness and expand market reach. These findings confirm that empowering MSMEs based on preparing financial reports and digital marketing makes a real contribution to the economic, social and environmental sustainability of the Sungai Bangkal Village community.